Introduction to NJWS 2024-4 - Buch, Anders (Nordic Journal of Working Life Studies, 2024)
Welcome to the fourth and final issue of Nordic Journal of Working Life Studies for 2024. This edition features four research articles authored by scholars from Finland, Sweden, Norway, and Denmark.